The wolf hunt : a novel - Gundar-Goshen, Ayelet, 1982- (Little, Brown and Company, 2023)
"Lilach has it all: a beautiful home in the heart of Silicon Valley, a successful husband and stable marriage, and a teenage son, Adam, with whom she has always felt a particular closeness. Israeli immigrants, the family has now lived in the U.S. long enough that they consider it home. But after a brutal attack on a local synagogue shakes their sense of safety, Adam enrolls in a self-defense class taught by a former Israeli Special Forces officer. There, for the first time, he finds a sense of confidence and belonging. Then, tragedy strikes again when an African American boy dies at a house party, apparently from a drug overdose. Though he was a high school classmate, Adam claims not to know him. Yet rumors begin to circulate that the death was not accidental, and that Adam and his new friends had a history with Jamal. As more details surface and racial tensions in the community are ignited, Lilach begins to question everything she thought she knew about her son. Could her worst fears be possible? Could her quiet, reclusive child have had something to do with Jamal's death?"--